-Role of Financial Derivatives in Rationalizing Investment Decisions- Field study on sample of brokerage firms in Khartoum stock of exchange - El Sayed, Abdel Salam Awad Khair; Hussein, Asaad Mubarak (Journal of Economic, Administrative and Legal Sciences, 2019)
The problem of the study represented in the lack of knowledge of many investors and participants in the Stock of Exchanges with the concept of financial derivatives, it advantages and its role in rationalizing investment decisions. The study aimed to state the concept of financial derivatives, its characteristics and its different contracts’ types, to study the relationship between financial derivatives and rationalizing investment decisions in the Stock of Exchanges. The study found that, decision maker’s full knowledge for financial derivatives, its types and the nature of any of it helps in rationalizing investment decisions, using long position option contracts contributes in rationalizing investment decisions. The study recommended increasing the awareness of participants in the Stock of Exchanges with financial derivatives and its advantages through conferences, symposiums and workshops.
Keywords: financial derivatives; investment decisions